Epistatic and independent functions of Caspase-3 and Bcl-X(L) in developmental programmed cell death - Roth, K. A. (The National Academy of Sciences, 2000)
The number of neurons in the mammalian brain is determined by a balance between cell proliferation and programmed cell death. Recent studies indicated that Bcl-X(L) prevents, whereas Caspase-3 mediates, cell death in the developing nervous system, but whether Bcl-X(L) directly blocks the apoptotic function of Caspase-3 in vivo is not known. To examine this question, we generated bcl-x/caspase-3 double mutants and found that caspase-3 deficiency abrogated the increased apoptosis of postmitotic neurons but not the increased hematopoietic cell death and embryonic lethality caused by the bcl-x mutation. In contrast, caspase-3, but not bcl-x, deficiency changed the normal incidence of neuronal progenitor cell apoptosis, consistent with the lack of expression of Bcl-X(L) in the proliferative population of the embryonic cortex. Thus, although Caspase-3 is epistatically downstream to Bcl-X(L) in postmitotic neurons, it independently regulates apoptosis of neuronal founder cells. Taken together, these results establish a role of programmed cell death in regulating the size of progenitor population in the central nervous system, a function that is distinct from the classic role of cell death in matching postmitotic neuronal population with postsynaptic targets.